PhD Project on knowledge management and intellectual capital - Curado, Carla (2003)
Bontis et al. (2002) suggest that intellectual capital represents the “stock” of knowledge that exists in an organization. Managing this stock of knowledge in the firm is the domain of knowledge management (Choo and Bontis, 2002). There are different dimensions of intellectual, and flows between them. There must be made a fundamental distinction between stocks and flows of knowledge (Dierickx and Cool, 1989), (Roos and Roos, 1997), (Bontis et al., 1999). Knowledge is a puzzling concept, tough to measure (Spender, 2002). Value is created when stocks of knowledge are employed and degrades when they remain unused (Pike et al., 2002). Knowledge assets are not consumed when they are applied to solving organizations problems, on the contrary, a knowledge asset´s value is generally maintained and often enlarged by its application, while conventional assets must be depreciated or replaced (Spender, 2002). Thus, knowledge management is a strategic issue (Nonaka and Konno, 1998), (Alvarez and Barney, 2001), (Bontis and Nikitopoulos, 2001).